Top-down versus bottom-up and the Ruritanian bean bug - Hassell, M. P. (The National Academy of Sciences, 1998)
In a recent article, Hunter uses the late George Varley and George Gradwell’s long-term data on the winter moth (Operophtera brumata) and green tortrix (Tortrix viridana) populations to propose a method of quantifying the relative importance of top-down effects (because of natural enemies) and bottom-up effects (because of resource competition) in influencing population dynamics. We believe this approach is deeply flawed. Using Varley and Gradwell’s winter moth study, we show that the problems with Hunter’s analysis lie in his misinterpretation of the population dynamics and his inappropriate use of statistical techniques. We also emphasize the importance of distinguishing clearly between two quite different things: firstly, top-down and bottom-up regulation of populations and secondly, the much simpler task of categorizing factors affecting changes in population density as either top-down or bottom-up processes.